Preventive measures for arterial hypertension risk factors among medical staff of Feofaniya Clinical Hospital of State Management of Affairs - Hordienko, L.; Perepadya, O.; Zukow, W. (Journal of Education, Health and Sport, 2018)
Researches conducted in different departments of Feofaniya Clinical Hospital in recent 5 years suggest extremely wide prevalence of arterial hypertension. According to the data of the representative extract survey the age-standardized prevalence of arterial hypertension at the hospital is 39.9% among men and 41.1% among women.